The plant model system Arabidopsis set in an evolutionary, systematic, and spatio-temporal context - Koch, Marcus (The journal of experimental botany, 2019)
The genus Arabidopsis as currently described consists of ~15 species. All relatives of A. thaliana evolved during Pleistocene glaciation and deglaciation cycles
Published: 27 September 2018
Gesehen am 11.10.2019